Punishments and Violations in Character Development: Management Practices at Madrasah Tsanawiyah (MTs) Darul Hikam Seputih Banyak - Soleh Hidayat; Muhammad Yusuf (Yayasan Haiah Nusratul Islam, 2026)
This study analyzes how punishments and violations are managed as part of character development among students at MTs Darul Hikam Seputih Banyak, Central Lampung. The study responds to recurrent student violations, including truancy, damage to school facilities, low honesty in learning activities, and formalistic participation in religious practices. This research employs a qualitative field approach with descriptive analysis. Data were collected through observation, in-depth interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings show that character development is planned through value formulation, mapping of student violations, integration into learning and habituation programs, and the formulation of graduated educative sanctions. Implementation is carried out through teacher exemplarity, religious routines, classroom integration, school regulations, corrective guidance, and parental involvement. Evaluation is conducted through continuous behavioral observation, feedback, rewards, and follow-up meetings. The study concludes that punishments and violations become meaningful instruments of character formation when managed as educative, restorative, and participatory processes rather than as punitive control alone.